Exiles in the Sahara - Frost, Kelman (Abelard-Schuman, 1964)
The Chebka, that part of the Sahara into which twelve-year-old Hassoun and his people fled, is now known as the M'Zab, and the people living there, direct descendants of the Ibadites, are usually called Mozabites. This story tells of the founding in the the eleventh century of El-Ateuf, the first Mozabite settlement after their exile in the desert within a desert.
Keywords: Littérature -- Mzab

Récits du Mzab: textes berbères de l'Oued-Mzab et traductions - Dallet, Jean-Marie (Fichier de documentation berbère, 1965)
Keywords: Littérature -- Mzab